The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1080/00379271.2012.10697762
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of the genusMorphoFabricius 1807: insights from two mitochondrial genes (Lepidoptera: Nymphalidae)

Abstract: Abstract. Two phylogenies of Morpho butterfl ies were previously published, founded on morphological data analysis. These phylogenies shared similarities but also several differences. In the present study we used partial sequences of the CO1 and Cyt b mitochondrial genes to infer the phylogenetic relationships between the subgenera. From the ten subgenera previously described, seven are shown to be monophyletic: Iphimedeia, Laurschwartzia, Iphixibia, Megamede, Grasseia, Balachowskyna and Deyrollia. Although no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(50 citation statements)
references
References 28 publications
(28 reference statements)
6
44
0
Order By: Relevance
“…This study showed that CO I gene alone was not enough to produce synapomorphies on each node but this gene was able to show a good support for a certain closely-related species. Previous study showed the mitochondrial gene CO I was very useful when combined with Cytochrome b to resolve the relationships in the genus Morpho (Nymphalidae) (Cassildé et al, 2012), or when combined with CO II in the genus Papilio (Caterino and Sperling, 1999). In addition, the combination of the CO I and EF-1α increased resolution and supports most of the phylogenetic relationships suggested by separate analysis of Ectoedemia s. str.…”
Section: Discussionmentioning
confidence: 81%
“…This study showed that CO I gene alone was not enough to produce synapomorphies on each node but this gene was able to show a good support for a certain closely-related species. Previous study showed the mitochondrial gene CO I was very useful when combined with Cytochrome b to resolve the relationships in the genus Morpho (Nymphalidae) (Cassildé et al, 2012), or when combined with CO II in the genus Papilio (Caterino and Sperling, 1999). In addition, the combination of the CO I and EF-1α increased resolution and supports most of the phylogenetic relationships suggested by separate analysis of Ectoedemia s. str.…”
Section: Discussionmentioning
confidence: 81%
“…We selected 119 sequences from two previously published datasets (Cassildé et al. ; Penz et al. ) and complemented this dataset with 24 additional nuclear sequences (see Supporting Information S1).…”
Section: Methodsmentioning
confidence: 99%
“…Although the genus has received recent attention to resolve phylogenetic relationships (Penz and DeVries ; Cassildé et al. , ; Penz et al. ; Blandin and Purser ), a completely resolved phylogenetic tree is still lacking.…”
mentioning
confidence: 99%
“…Penz & DeVries (2002) hypothesized that all species with larvae that feed on monocotyledonous plants represented early branches of the Morpho phylogeny, implying a single evolutionary switch to eudicot‐feeding. In contrast, the analysis by Cassildé et al (2010) implied a pattern of host plant use where eudicot‐feeding habits evolved once and was subsequently reversed. Forest species of Morpho are known to have distinct vertical distributions where the males of some glide at or above the forest canopy level, and others fly at lower strata.…”
Section: Introductionmentioning
confidence: 96%